Hardcore fans in hardcore times: violence in peruvian soccer - Arboccó de los Heros, Manuel (2013)
The phenomenon of the barras bravas is already a problem in the country for approximately two decades. In recent years, the problem seems to overflow to the population and to the State itself. Some propose only measures police and punitive. Others, however, point to an academic speech to intervene from the roots of the problems of family and social violence suffered by many so-called modern societies. The present article will define the problem, its causes will be analyzed and consequences be remembered. Some cases painful for victims and perpetrators, and will finally propose some recommendations, from a multidisciplinary perspective to amend the difficult situation.